Networking of educational inspection: the "INSPECTIO" platform in Andalusia - Pedro Ángel Luna Ariza; Eufrasio Amador Castellano Luque (ADIDE Federación, 2014)
A look to the future of Educational Inspection demands to put the attention in the internal processes of organization and functioning. The model of inspector which work is realized to the margin of the rest of his companions has expired. The current tools that provide to us the new technologies of the information and the communication facilitate our daily occupation and improve the possibilities of coordination in the equipment and services. The possibilities to work in network of the inspectors of education in Andalusia using Inspectio Platform it is a good example of it. After a normative foundation and a conceptual approximation, we try to explain this tool, using a descriptive and practical methodology.